Socio-economic study of the community in the Ternate Nusantara Fisheries Port (NFP) area, North Maluku Province - Massiseng, Andi Nur Apung; Syamsuddin, Suryani; Sasole, Hasanati Safitri; Surachmat, Agus; Suleman, Yakup (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2024)
Socio-economic studies are closely related to society, their needs, and how to fulfill them. One way society can meet its needs is by processing natural resources, such as agricultural and fishery activities. Agricultural and fishery activities that do not pay attention to conservation principles can cause land degradation, such as erosion, landslides, and extinction of natural resources. Socio-economic studies influence people's behavior in managing natural resources to meet basic needs. North Maluku Province has an area of 145,801.10 km² and is surrounded by estuary waters. The purpose of this study was to determine the socioeconomic conditions of coastal communities domiciled in the Ternate Nusantara Fisheries Port (NFP) Area, North Maluku Province. This research was conducted from January 2024 - to March 2024 at the Ternate Nusantara Fisheries Port (NFP) Ternate, North Maluku Province. The research methods used were observation, interviews, and questionnaires processed using a Likert scale. The results of this study indicate that the income of fishermen is highly dependent on weather conditions during fishing, while their expenses are related to the cost of fishing equipment and the fishermen's lifestyle. The higher the income earned, the greater the expenses.  The community who do not work as fishermen, the processing industry plays a very important role as the main job that can increase income around the Ternate Nusantara Fisheries Port (NFP).